ANNA BOLEYN I REFORMATORSKI OBÓZ HUMANISTÓW - Smoluk, Marek (In Gremium. Studies in History, Culture and Politics, 2010)
ANNE BOLEYN AND HER REFORMATORY FACTION OF HUMANISTS Annc Bolcyn is usually associatcd with Henry VIII’s second wife and mother of Elizabeth- thc future Queen of England. Anne Boleyn’s position as an advocate of reforms and patron of Protestants is often omitted in numerous historical works. The principal aim of this paper is to present her in this less commonly known light and assess thc activities of her reformatory faction The paper provides evidence that Queen Anne was more than the mere second wife of Henry VIII. The radical reformers under her leadership contributed greatly to the English Reformation and Anne Boleyn’s political and religious role in it is undoubted and sometimes underestimated.